A State-of-the-Art Decentralized Structure for Unit Commitment in Restructured Power Systems - Rasouli, Ali; Bigdeli, Mehdi; Malekshah, Soheil; Ansari, Javad (Journal of power technologies, 2024)
In a restructured power system, different parts of the network are dedicated to the private sector and each of these sectors seeks to maximize their profits. Therefore, it cannot be traditionally planned and managed by the network and a new framework needs to be used. In this paper, a decentralized framework for the planning of generation units is presented. In this framework, the power system is divided into several subsets and each of these subsets has a physical relationship involving the exchange of active and reactive power and the transmission of information as well as economic information with each other. Thus, a hierarchical bi-level optimization method is used to implement the decentralized decision method to solution the security constraints unit commitment (SCUC) problem. Considering dispersed generation (DG) units in calculations will reduce the total cost of generation. Generally, the cost of generating power in such units is less than that of large units. The proposed method is implemented on a sample 6-bus network, which has an active and passive distribution network. The results indicate the correctness and accuracy of this method.